The performance of Micro, Small and Medium Enterprises sector in the era of ASEAN-China Free Trade - Susanti, Susanti (Technium Social Sciences Journal, 2021)
Micro, Small, and Medium Enterprises (MSMEs) have a very large role in the Indonesian economy, in terms of its contribution to the output (GDP), employment, and gross fixed capital formation (investment). Nevertheless, the ASEAN-China free trade is thought to have a negative impact on the performance of MSME sectors in Indonesia, one of the indicators is declining contribution of MSMEs in non-oil exports of Indonesia. This study is intended to give an overview of the MSME sector performance during the implementation of the ASEAN-China free trade. This research is descriptive qualitative research, aimed to analyze qualitatively and presents the performance of MSME sector during the implementation of the ASEAN-China free trade. Based on data analysis that has been done, it is concluded that the performance of MSME sector in Indonesia has decreased during the implementation of the ASEAN-China free trade. This can be seen from several indications that the first, decreasing the contribution of MSME sector to Gross Domestic Product (GDP). Second, the decline in the contribution of MSME sector in employment of the total labor force working in Indonesia. Third, the contribution of MSME sector in non-oil exports Indonesia tend to decrease.